Educare al rispetto. National Guidelines in vocabulary of a sample of Italians schools’ PTOF - Szpunar, Giordana; Sposetti, Patrizia; Marini, Sara; Marini, Sara (Formazione & insegnamento, 2019)
Gender education is an important tool to promote equal opportunities and respect for differences. In line with this perspective, the Ministry of Education, University and Research (MIUR) has recently issued the National Guidelines “Educare al rispetto: per la parità tra i sessi, la prevenzione della violenza di genere e di tutte le forme di discriminazione” (2015). According to the Comma 16 of the Law 107/2015, the Guidelines aims at implementing the principle of equal opportunities in the schools by promoting its adoption in the Piano Triennale dell’Offerta Formativa (PTOF). The paper presents an exploratory study concerning the text analysis of 100 causally selected PTOF. In particular, we have used the T-LAB software (version 9.1.5) to compare these texts with some key lexical features of the National Guidelines. Collected data suggest that exists a partial overlap between the National Guidelines and the actions for equal opportunities realized by the schools and described in their PTOF. This overlap becomes relevant if we consider not only the thematic content concerning the expression “equal opportunities”, but also the one concerning the expression “discrimination”.